New record of Thor hainanensis Xu & Li, 2014 and taxonomical remarks on Lysmata ternatensis de Man, 1902 (Decapoda: Thoridae & Lysmatidae) from the Lakshadweep Islands, India - Madhavan, Manu; Purushothaman, P.; Akash, S.; Bharathi, S.; Jose, Sheena; Dhinakaran, A.; Ravi, Charan; Kumar, T.t. Ajith; Lal, K. K. (Zootaxa, 2019)
The present study reports the new record of Thor hainanensis Xu & Li, 2014, on the basis of material from Agatti Islands in the Lakshadweep, India. This species was recently described from Hainan Island, China. Relationship of this species to two closely related species (T. paschalis and T. amboinensis) is discussed in this manuscript. Similarly, the present study also reports the rediscovery of other species, Lysmata ternatensis De Man, 1902 from the Lakshadweep waters with detailed taxonomic description. The present specimens were found to occur in the intertidal region in small crevices and rocks at a depth of 0.5-2.0 m. Genetic analysis using the mitochondrial COI sequences for both the species reveals close agreement for the morphological identification and showed the significant variation from the closely related species.